2014
DOI: 10.1063/1.4876078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of vapor-deposited polymer glasses

Abstract: We have investigated the properties of vapor-deposited glasses prepared from short polymer chains using molecular dynamics simulations. Vapor-deposited polymer glasses are found to have higher density and higher kinetic stability than ordinary glasses prepared by gradual cooling of the corresponding equilibrium liquid. In contrast to results for binary Lennard-Jones glasses, the deposition rate is found to play an important role in the stability of polymer vapor-deposited glasses. Glasses deposited at the slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…We find that for T s > 850K the two different types of glasses have comparable densities whereas for T s < 850K the PVD glasses have a larger density than the melt-quenched glasses by up to 1.5%. The lower potential energy and the higher density of the PVD glasses are in good agreement with experimental findings for the ultrastable organic glasses [8,20], which shows that the stability in the two classes of materials follow a similar trend.…”
Section: Resultssupporting
confidence: 88%
“…We find that for T s > 850K the two different types of glasses have comparable densities whereas for T s < 850K the PVD glasses have a larger density than the melt-quenched glasses by up to 1.5%. The lower potential energy and the higher density of the PVD glasses are in good agreement with experimental findings for the ultrastable organic glasses [8,20], which shows that the stability in the two classes of materials follow a similar trend.…”
Section: Resultssupporting
confidence: 88%
“…The simulated vapor deposition process is analogous to that reported earlier (9,32). Iterative cycles are repeated until a film with thickness of ∼35 σ bb is grown.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas one might expect all glasses to be isotropic because of their structural disorder, Yokoyama et al and other groups have shown that molecular orientation in vapor-deposited glasses can be quite anisotropic (3,4,8,9) and depend upon deposition conditions (3). It has recently been suggested that orientation resulting from deposition could be used as a figure of merit to identify promising compounds for these applications (10).…”
mentioning
confidence: 99%
“…[1][2][3] In particular, physical vapor deposition can prepare organic glasses with exceptional thermal stability if the deposition conditions are chosen appropriately; [4][5][6] transformation to the supercooled liquid has been observed to occur at temperatures up to 35 K higher than the glass transition temperature (T g ) of the liquidcooled glass. 7 Stable glasses also have high density 6,[8][9][10][11] and low enthalpy [5][6][7][12][13][14][15] and can exhibit useful anisotropic structures 16 as evidenced by birefringence, 10,11,17 dichroism, 17 and X-ray scattering. 14,15,18,19 These solid-state properties are lost on transformation to the equilibrium supercooled liquid, so high thermal stability is important for extending the range of applications for these materials.…”
Section: Introductionmentioning
confidence: 99%